Democracy In Islam from The Political to The Religious and Ethical Perspective: Turkiye as A Model - Alrefai, Ayman Kassem; Abdulwahab Murshed, Amer; Syed Ismail, Sharifah Hayaati (Online Journal of Research in Islamic Studies, 2023)
The study discusses the problem of democracy in Islam, from the political to the religious and ethical perspective in an Islamic country with a strict secular system (Turkiye). The study is aiming to monitor the role of democracy as a fair movement for peoples, especially Muslims, in secular regimes, in which it affects their lives by reconstructing the political system and its legislations and authorities in a way that consider their beliefs and moral ethics. Taking that into consideration as Muslims to answer the question: Can we, as Muslims, take a fair stance on democracy and other Western theories that can be benefited the lives of Muslims? As an analytical study, we will follow the Qualitative Methodology to achieve the goal of the study, which led us to the result of elaborating on the possible ways to benefit as Muslims from political concepts particularly democracy without allowing for these Western concepts to eliminate Islam and its ethics from our lives from one hand or make the extremists Muslims alienate others from this religion from another hand; by considering two main points: 1) Being convinced of the historicism of political practice in Islam and reconsidering the legal texts according only to Islamic ethics and the Shariah objectives. 2) Dismantling the relevant terms coming to us and activating the functional view of these interests and their abstract principles and giving them priority over the textual and idiomatic definition. Therefore, it is necessary for us as Muslims to develop new concepts in politics which are compatible with Islam and its ethical principles and stem from reality and civilizational requirements, to play the leading role in achieving both intellectual and applied advancement for the Muslim nation, which leads it to return to the forefront of its civilized role that combines Islamic values and civilized development.